Common interest groups: The power of connection - International Livestock Research Institute (International Livestock Research Institute, 2022)
For the Livestock Livelihoods and Agri-food Systems Flagship, the ‘Livestock-led interventions towards equitable livelihoods and improved environment in the Northwest Highlands of Vietnam’ or Li-chăn project established five common interest groups (CIGs), with more than 60 beneficiary households in the Chieng Chung and Chieng Luong communes.